Syndecan‐4 Enhances Therapeutic Angiogenesis after Hind Limb Ischemia in Mice with Type 2 Diabetes. Issue 9 (18th February 2016) - Das, Subhamoy; Monteforte, Anthony J.; Singh, Gunjan; Majid, Marjan; Sherman, Michael B.; Dunn, Andrew K.; Baker, Aaron B.
Abstract : Delivering syndecan‐4 with FGF‐2 improves the effectiveness of FGF‐2 therapy for ischemia in the diabetic disease state. The syndecan‐4 proteoliposomes significantly enhance in vitro tubule formation as well as blood perfusion and vessel density in the ischemic hind limbs of diseased ob/ob mice. Syndecan‐4 therapy also induces a marked immunomodulation in the tissues, increasing the polarization of macrophages toward the M2 phenotype.